Exploring Social Media Citizen Journalism Optimization in Karang Taruna as Indonesian Youth Organizations - Yasundari, Yasundari; purwaningwulan, Melly Maulin; Saputra, Sandi Jaya (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2026)
This study explores the optimization of social media–based citizen journalism within Karang Taruna as Indonesian youth organizations. Using a qualitative approach, the research combines netnography and in-depth interviews among selected participants from Bandung City, Bandung Regency, and West Bandung Regency. The findings indicate that the optimization of social media–based citizen journalism in Karang Taruna is comprised of three interrelated dimensions: (1) Production aspect such as regular production of visual contents (images and short videos) depicting events in their community; (2) Narrative aspect, storytelling based on the context of the issue that reflects the identity of the community; and (3) Participatory aspect, active participation in the planning and distribution process. Nonetheless, the optimization process is still partial because of limited resources, unequal digital literacy skills, and imprecise management of content development